2013
DOI: 10.4018/jmcmc.2013010104
|View full text |Cite
|
Sign up to set email alerts
|

Path Loss Model Tuning at GSM 900 for a Single Cell Base Station

Abstract: Mobile communications has become an everyday commodity. In the last decades, it has evolved from being an expensive technology for a few selected individuals to today’s ubiquitous systems used by a majority of the world’s population. Imprecise propagation models lead to networks with high co-channel interference, as well as power waste. This study aims to adapt a propagation model in the city of Nablus (Palestine) for a GSM frequency band. This study helps to design better GSM networks for the city in spite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Path Loss dB = Ptot -RSRP (5) Path Loss dB = Gt+Pt-Gr-Cl-Fl-(10*log (Nrb)-10*log ( 12))-RSRP (6)…”
Section: (B) Measurement Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Path Loss dB = Ptot -RSRP (5) Path Loss dB = Gt+Pt-Gr-Cl-Fl-(10*log (Nrb)-10*log ( 12))-RSRP (6)…”
Section: (B) Measurement Toolsmentioning
confidence: 99%
“…From the results, the authors observed a difference of 12.6dB between the two compared models. An approach to adapt Standard Macrocell model and Bertoni-Walfisch model for GSM radio networks design is presented in [5], using city of Nablus, Palestine as a case study. From the results, Bertoni-Walfisch model outperform the Standard Macrocell model by about 60%.…”
Section: Introductionmentioning
confidence: 99%
“…Chhaya Dalela, Prasad and P. K. Dalela used a linear iterative method of least square theory to tune Cost-231 Hata model in different environments [5]. Mousa, Dama, Najjar and Alsayeh performed the optimization using least square method for standard macro cell model and Walfisch-Bertoni model [6]. Joseph and konyeha developed an optimized Hata model for prediction of path loss experienced by CDMA2000 signals in South-Nigeria [7].…”
Section: Introductionmentioning
confidence: 99%